2002
DOI: 10.1074/jbc.m203287200
|View full text |Cite
|
Sign up to set email alerts
|

Negative Regulation of Platelet Clearance and of the Macrophage Phagocytic Response by the Transmembrane Glycoprotein SHPS-1

Abstract: SHPS-1 is a receptor-type glycoprotein that binds and activates the protein-tyrosine phosphatases SHP-1 and SHP-2, and thereby negatively modulates intracellular signaling initiated by various cell surface receptors coupled to tyrosine kinases. SHPS-1 also regulates intercellular communication in the neural and immune systems through its association with CD47 (integrin-associated protein) on adjacent cells. Furthermore, recent studies with fibroblasts derived from mice expressing an SHPS-1 mutant that lacks mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
107
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(113 citation statements)
references
References 45 publications
4
107
2
Order By: Relevance
“…Moreover, we found that thioglycollate, a reagent commonly used to elicit macrophages in the peritoneum, activates PEM phagocytosis toward RBCs (Fig. 3H), explaining the seemingly discrepant results reported by others (28).…”
Section: In Vivo Assessment Of Macrophage Phagocytosis By Adoptivecontrasting
confidence: 37%
See 1 more Smart Citation
“…Moreover, we found that thioglycollate, a reagent commonly used to elicit macrophages in the peritoneum, activates PEM phagocytosis toward RBCs (Fig. 3H), explaining the seemingly discrepant results reported by others (28).…”
Section: In Vivo Assessment Of Macrophage Phagocytosis By Adoptivecontrasting
confidence: 37%
“…Resolution of at least two puzzles remains paramount: first, why macrophages do not attack self in mice deficient of Cd47 or Sirpα? Despite that the Cd47-Sirpα-mediated inhibition is missing, mice deficient of Cd47 (26), Sirpα (established in this study), or the Sirpα cytoplasmic domain (27) are relatively healthy, manifesting no or only minor phenotypes (9,18,28) that suggest macrophage phagocytosis toward self-cells. Adoptive transfer of Cd47-null RBCs into these mutant mice also failed to induce rapid elimination (1) (also shown in this study).…”
Section: Significancementioning
confidence: 99%
“…6,9 CD47 on target cells interacts with SIRPa on macrophages and transmits a 'don't eat me' signal through SH2 domain-containing phosphatases, SHP-1 and -2, and results in the inhibition of target cell phagocytosis. 7,28,29 CD47 is expressed at lower levels on bone marrow resident hematopoietic stem cells (HSCs) than on circulating HSCs. However, when bone marrow HSCs were mobilized out of bone marrow, they upregulated CD47.…”
Section: Discussionmentioning
confidence: 99%
“…Given the role of SHPS-1 in cytoskeletal reorganization (20,21) and the fact that B16F10 cells are highly motile whereas Melan-a cells are not (30), we focused our attention on the effect of CD47 binding to SHPS-1 on cell migration. Quantitative analysis with a Boyden chamber assay revealed that the number of Melan-a cells that migrated through a membrane coated with fibronectin was reduced by ϳ20% in the presence of CD47-Fc (Fig.…”
Section: Differential N-glycosylation Of Shps-1 In Mouse Nontumorigenmentioning
confidence: 99%
“…SHPS-1 negatively or positively regulates intracellular signaling initiated either by tyrosine kinase-coupled receptors for growth factors or by cell adhesion to extracellular matrix proteins (18,19). With the use of mice lacking most of the cytoplasmic region of SHPS-1 (20,21), we recently showed that this protein plays an important role both in integrin-mediated cytoskeletal reorganization and in cell migration. In addition, studies with dominant negative or loss-of-function mutant proteins have established SHP-2 as a signaling component essential for cell adhesion and migration as well as cytoskeletal organization (22)(23)(24)(25)(26).…”
mentioning
confidence: 99%